Bahasa Inggris - Hasyim, Muhamad Ardi Nupi; Ramdhany, Muhamad Arief (Jurnal Minds: Manajemen Ide dan Inspirasi, 2024)
This study examines how spiritual leadership curbs fraud in Indonesian financial service companies through the mediating role of organizational culture and the moderating role of employee motivation. Using a quantitative design, data were collected from 220 employees across banking and non-banking institutions through a five-point Likert survey. The hypotheses were tested using Partial Least Squares (PLS) analysis. Results show that spiritual leadership exerts a significant direct and indirect effect on fraud prevention via organizational culture. While employee motivation does not moderate the link between spiritual leadership and fraud prevention, it strengthens the relationship between organizational culture and fraud prevention. The findings underscore the importance of embedding spiritual leadership and cultivating an ethical organizational culture to reinforce integrity systems, with employee motivation acting as a vital reinforcing factor.